First-generation undergraduate researchers: understanding shared experiences through stories - Henrichsen, Christine M.; Keenan, Susan M. (Frontiers in Education, 2023)
If you want to know a person, you need to know their story. If institutions want to better support their students, they need to know them, and therefore need to know their stories. First-generation students, a vital part of our academic communities, model qualities such as hard work, optimism, and perseverance. Academic settings, policies, and hidden curriculum present challenges for first-generation students and often result in inequitable outcomes. Undergraduate research experiences (UREs) are one resource institutions have to support these students. Little is known of the first-generation student experience in UREs. Using in-depth interviews, we collected the stories of first-generation biology students who had participated in UREs. A thematic analysis illuminated five themes of shared experiences: what to expect in college, parental support, intent to apply to medical school, mentorship, and becoming a researcher. Stories provide depth and details into these themes that cannot be highlighted using other methodologies. We share detailed accounts of the experiences of two first-generation students. By using portions of the original conversations, the students tell their stories in their own voices. A dialogical method was used to juxtapose the two stories and to increase opportunities for reader reflexivity and introspection. We discuss how the stories relate to the literature and reflect on the power of that gathering and sharing stories of first-generation students' experiences.Introduction "If we want STEM to support the entirety of our diverse society, we must first employ a decent representation of that diversity in these fields." -Jackie O'Hara Although no two people are the same, there are common threads that bind us together as humans. And these threads, this understanding of what makes us human, are often found in the telling and hearing of stories. Nasser (2018) reminds us, "There are, effectively, an infinity of stories out there, just waiting to be found and told." If you were to answer the question, 'Why are you reading this article,' what would you say? Whatever the reason, there is a story that leads up to why you are here. Stories provide us with reflections and details into lived experiences that can